Alginates: From the ocean to gastroesophageal reflux disease treatment - Bor, Serhat; Kalkan, İsmail Hakkı; Çelebi, Altay; Dinçer, Dinç; Akyüz, Filiz; Dettmar, Peter; Özen, Hasan (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Bor S, Kalkan İH, Çelebi A, et al. Alginates: From the ocean to gastroesophageal reflux disease treatment. Turk J Gastroenterol 2019; 30(Suppl 2): S109-36.